Surface Treatment and Bioinspired Coating for 3D-Printed Implants - Liu, Junyi; Mohd Rafiq, Nafisah Bte; Wong, Lai Mun; Wang, Shijie (Frontiers in Chemistry, 2021)
3D printing technology has developed rapidly and demonstrated great potential in biomedical applications. Although 3D printing techniques have good control over the macro-structure of metallic implants, the surface properties have even superior control over the tissue response. By focusing on the types of surface treatment, this enhanced the osseointegration activity between bone-implant interface. Therefore, this review paper aims to discuss the surface functionalities of metallic implant regarding its physical structure, chemical composition and biological reaction through its surface treatment and bioactive coating. Perspective about the current challenges and future directions for development of surface treatment on 3D printed implant is also presented.